O brasão e o ramo de café: migração, simbologia e identidade no município de Matelândia 1950-1980 - Dezordi, Maurício (2015)
This paper discusses the migration and identity construction process in the municipality of Matelândia - PR, between the period 1950 to 1980 based on the analysis of the old coat of arms municipality of Matelândia, and the symbolic representation of the coffee business in its coat. Seeking initially investigate the migration process and the establishment of immigrant agricultural colonies in southern Brazil. Analyzing the agricultural colonies and the westward migration of Paraná, we discuss the existence of symbolic boundaries and building a local territorial identity in the municipality of Matelândia. Where is noticeable presence of alterity relations from the presence of a coffee business in the old coat of arms municipality. Based on the methodology of evidential paradigm Ginzburg, searched through clues, find out how to build the image of migrant settler and how it was founded the ideology of progress through work. Another issue discussed is the association between coffee cultivation and the culture and work system in Northern migrant Matelândia. Considering the presence of these groups of northern migrants in northern city of Matelândia. Region located in the old coat of arms municipal just where the coffee business was represented. Coffee cultivation in the region although cultivated by Southerners, was associated with culture and the Northern migrant.